Effect of entrepreneurial orientation on business performance of young women agribusiness owners in Benin: Do social and business environments matter? - DOSSOU, Smith; Adeoti, Razack; AOUDJI, KOSSI NOUNAGNON AUGUSTIN; DJANA, Mignouna (My University, 2021)
This research examined how key entrepreneurial orientation (EO) dimensions influence business performance of young women agribusiness owners, as well as the moderating effects of social and business environments on these relationships. Data were collected from a sample of 365 young women agri-food processing business owners in Benin. Moderated multiple regression methods were used to test multiple hypotheses including the interaction effects of social and business environments. The three EO dimensions identified in the context of young women agribusiness owners, namely Innovative EO, Pro-active EO and Risk-taking EO, positively influence business performance. The joint effect of EO and social environment on business performance was not significant. In contrast, the business environment negatively moderates the relationship between EO and business performance. Furthermore, there is a three-way interaction between EO, social and business environments, such that these young women entrepreneurs achieve low level of performance when adopting EO in social and business environments with high levels of barriers. The training of potential young women agribusiness owners on the appropriate EO, and the establishment of an innovation platform to jointly draft and implement action plans could enhance the performance of young women agribusiness owners. This study provides a critical understanding of what EO dimensions to stimulate for increased economic success of young women agribusiness owners. It also highlights the specific conditions for the effectiveness of EO on business performance of these entrepreneurs in developing contexts such as Benin.
Keywords: innovativeness; performance; pro-activenessrisk-taking; small-medium agribusinesses